The Role of Stock Market Development on Economic Growth in OPEC Countries: Does Oil Price Movement Matter? Fresh Evidence from Nigeria - Okere, Kingsley; Ndubuisi, Paul (Asian Journal of Economic Modelling, 2017)
This study investigates the relationship link crude oil price and stock market development and economic growth in one of the OPEC countries with emphasis on Nigeria over the period 1981 to 2014, using the latest methodology autoregressive distributed lag approach (ARDL) to cointegration analysis. Three indicator of stock market development are constructed using principal component analysis. The revels the dominant role of rule oil price as one of the engine for economic growth in Nigeria. Using inflation and trade openness as a moderator on economic activities in Nigeria, this study found that stock market is insignificant in driving economic growth in Nigeria indicating poor financial sector performance. In general, the results highlight the dominant role crude oil price and posits the weakness of the stock market in stimulating economic growth through resource mobilization and allocation in Nigeria. Therefore for government to achieve sustainable economic development and maximize stock market performance, policy maker in oil exporting countries should monitor the movement of crude oil prices.